BAHAYA SIARAN TELEVISI BAGI MASYARAKAT, INDIVIDU DAN BUDAYA ACEH - Hamdani, Hamdani (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2019)
Television is one of the audio visual mass media which is believed to have a very extraordinary power of influence, both cognitive (knowledge), affective (attitude) and behavioral (behavior). This influence does not only affect individual viewers, but also society and culture. The influence does not only take place positively, but the negative influence which is very detrimental to the community, individuals and local culture in the East. Among the mass communication theories that believe in the negative influence of television mass media are First, norm cultural theory which assumes mass media has the power to destroy a culture and replace it with a new culture of import through Western broadcast programs; Second, cultivation theory which believes that the mass media has the ability to embed, obscure and deflect fiction and even fabricate facts into every television broadcast on the understanding of ordinary viewers; and Third, cultural imperialism theory, which assumes that imported television broadcast programs always contain Western cultural values, which in turn obscure and eliminate native culture. Not to mention the television broadcast (generally private) that ignores the value of information, education and moral values as well as violence that is watched all the time by various groups ranging from children, women and Muslim communities. That is why the role of KPI (Indonesian broadcasting commission) is needed to tighten supervision and licensing for recalcitrant broadcasting institutions, so that they always adhere to broadcasting regulations.